2014
DOI: 10.1155/2014/478641
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CXCL16 Expression Suppresses Migration and Invasiveness and Induces Apoptosis in Breast Cancer Cells

Abstract: Background. Increasing evidence argues that soluble CXCL16 promotes proliferation, migration, and invasion of cancer cells in vitro. However, the role of transmembrane or cellular CXCL16 in cancer remains relatively unknown. In this study, we determine the function of cellular CXCL16 as tumor suppressor in breast cancer cells. Methods. Expression of cellular CXCL16 in breast cancer cell lines was determined at both RNA and protein levels. In vitro and in vivo studies that overexpressed or downregulated CXCL16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Immunohistochemistry and flow cytometry analyses showed that SR-PSOX/CXCL16 was located predominantly in the membrane and cytosol of RCC cell lines (Gutwein et al, 2009). In line with these clinical data, overexpression of TM-CXCL16 in breast cancer MDA-MB-231 cells suppressed their invasiveness in vitro and tumorigenesis in vivo (Fang et al, 2014). IR can upregulate the expression of TM-CXCL16 and promote the shedding of sCXCL16, which results in improved therapeutic efficacy by recruiting CD8 + CXCR6 + effector T cells (Matsumura & Demaria, 2010; Matsumura et al, 2008).…”
Section: Scavenger Receptors In Cancer Immunobiologymentioning
confidence: 71%
“…Immunohistochemistry and flow cytometry analyses showed that SR-PSOX/CXCL16 was located predominantly in the membrane and cytosol of RCC cell lines (Gutwein et al, 2009). In line with these clinical data, overexpression of TM-CXCL16 in breast cancer MDA-MB-231 cells suppressed their invasiveness in vitro and tumorigenesis in vivo (Fang et al, 2014). IR can upregulate the expression of TM-CXCL16 and promote the shedding of sCXCL16, which results in improved therapeutic efficacy by recruiting CD8 + CXCR6 + effector T cells (Matsumura & Demaria, 2010; Matsumura et al, 2008).…”
Section: Scavenger Receptors In Cancer Immunobiologymentioning
confidence: 71%
“…The expression and role of CXCL16 in human malignancies have received increasing attention. Abnormal expression of CXCL16 was detected in various cancers, such as colorectal cancer (Kee et al, 2013), breast cancer (Fang et al, 2014), non-small-cell lung cancer (Liang et al, 2018), pancreatic cancer (Wente et al, 2008), and nasopharyngeal carcinoma (Zhu et al, 2015). The effects of CXCL16 in contributing to the malignancy of tumors seem to be dependent on tumor type.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CXCL16 in cancer is quite unclear, while studies claim that it acts as a regulator in metastasis and progression of cancer, studies have also shown that it suppresses migration and invasion by attracting CD8 lymphocytes to tumor and leads to induction of apoptosis [42,43]. Although an insignificant decrease in expression of FGF (acidic) was observed, it is known that FGF induces mitogenic and cell survival activities including cell growth, morphogenesis, tissue repair, tumor growth and invasion [44].…”
Section: Accepted Manuscriptmentioning
confidence: 99%